Enantioseparation of Au20(PP3)4Cl4 Clusters with Intrinsically Chiral Cores. (19th June 2018) - Zhu, Yanfei; Wang, Hui; Wan, Kaiwei; Guo, Jun; He, Chunting; Yu, Yue; Zhao, Luyang; Zhang, Yin; Lv, Jiawei; Shi, Lin; Jin, Renxi; Zhang, Xinxiang; et al.
Abstract: Au20 (PP3 )4 Cl4 (PP3 =tris(2‐(diphenylphosphino)ethyl) phosphine), abbreviated as Au20, is the only Au nanocluster with an intrinsically chiral core without a chiral environment (chiral ligands or Au‐thiolate staples), making it a unique object to understand chiral evolution and explore chiral applications. Unfortunately, the synthesized Au20 is racemic, and its enantiomers have not yet been separated. Herein, we report a supramolecular assembly strategy with α‐cyclodextrin (α‐CD) to afford enantiopure Au20 in bulk, and an enantiomer excess ( ee ) value of as‐separated Au20 of 97 %. As a result of its high purity, the distinctive optical activity of Au20, which originates from electronic transitions confined in chiral cores, is fully explored. Theoretical studies reveals that the enantioseparation results from the preferential self‐assembly of α‐CD with organic ligands on the surface of right‐handed Au20 .